Cardiac metastasis in a living patient with oral cancer. Issue 6 (December 2019) - Fujio, Hisami; Otsuki, Naoki; Horichi, Yuto; Yanagisawa, Shungaku; Nishio, Mari; Teshima, Masanori; Shinomiya, Hirotaka; Hashikawa, Kazunobu; Nibu, Ken-ichi
Abstract: Cardiac metastasis from head and neck cancers are very rare. Metastases to heart are mostly diagnosed at autopsy, and seldom found while patients are alive. Patients with cardiac metastasis do not present with specific symptoms in the early stages, and diagnosis is often delayed until the disease has advanced significantly. Here, we report a 66-year-old lady who was diagnosed with cardiac metastasis 10 months after surgical resection of oral cancer. She died one month following the discovery of cardiac metastasis. Cardiac metastasis should be considered when unexplained and progressive decline of general health is observed, even in the absence of abnormalities on the electrocardiogram. Early diagnosis may be made by analyzing the chronological changes in the cardiac accumulation of fluorodeoxyglucose during positron emission tomography–computed tomography scan.